The Evolution of Urban Concentration Around the World: A Panel Approach - Alejandro Gaviria; Ernesto H. Stein (Inter-American Development Bank, Research Department, 2000)
In this paper, we use a panel approach to study population growth in major cities around the world. We find that major cities grow faster in relatively backward economies and in more volatile, faster-growing economies. We also find that the effects of trade policy on the growth of major cities hinge heavily on geography. While population growth in major cities located at or near ports does not change after an upsurge of trade flows, population growth in landlocked major cities tends to slow down after the same event. On the other hand, we do not find any effect of political regime on the population growth of major cities. Finally, we find some evidence that, other things being equal, larger cities tend to grow at smaller rates.
Keywords: 330; Städtische Bevölkerungsentwicklung; Großstadt; Panelforschung; Welt